Magnetophotoluminescence study of GaAs/AlGaAs coupled double quantum wells with bimodal heterointerface roughness - Lopes, E. M. [UNESP]; Duarte, J. L.; Dias, I. F. L.; Laureto, E.; Guimaraes, P. S. S.; Subtil, A. G. S.; Quivy, A. A. (Elsevier B.V., 2012)
This work reports on the results of magnetophotoluminescence (MPL) measurements carried out in a sample containing two Al0.35Ga0.65As/GaAs, coupled double quantum wells (CDQWs), with inter-well barriers of different thicknesses, which have the heterointerfaces characterized by a distribution of bimodal roughness. The MPL measurements were performed at 4 K, with magnetic fields applied parallel to the growth direction, and varying from 0 to 12 T. The diamagnetic shift of the photoluminescence (PL) peaks is more sensitive to changes in the confinement potential, due to monolayer variations in the mini-well thickness, rather than to the exciton localization at the local potential fluctuations. As the magnetic field increases, the relative intensities of the two peaks in each PL band inverts, what is attributed to the reduction in the radiative lifetime of the delocalized excitons, which results in the radiative recombination, before the excitonic migration between the higher and lower energy regions in each CDQW occurs. The dependence of the full width at half maximum (FWHM) on magnetic field shows different behaviors for each PL peak, which are attributed to the different levels and correlation lengths of the potential fluctuations present in the regions associated with each recombination channel. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Magnetophotoluminescence; Coupled double quantum wells; GaAs/AlGaAs; Interface disorder; Potential fluctuations